Entrepreneurship, Innovation, and Technology A Holistic Analysis of Growth Factors - Rajagopal; Goncalves, Marcus; Zlatev, Vladimir (Palgrave Studies of Entrepreneurship and Social Challenges in Developing Economies, 2024)
XXXV, 467 p. 73 illus., 33 illus. in color.